Directional coupling of slow and fast hippocampal gamma with neocortical alpha/beta oscillations in human episodic memory - Griffiths, Benjamin J.; Parish, George; Roux, Frederic; Michelmann, Sebastian; van der Plas, Mircea; Kolibius, Luca D.; Chelvarajah, Ramesh; Rollings, David T.; Sawlani, Vijay; Hamer, Hajo; Gollwitzer, Stephanie; Kreiselmeyer, Gernot; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Episodic memories hinge upon our ability to process a wide range of multisensory information and bind this information into a coherent, memorable representation. On a neural level, these 2 processes are thought to be supported by neocortical alpha/beta desynchronization and hippocampal theta/gamma synchronization, respectively. Intuitively, these 2 processes should couple to successfully create and retrieve episodic memories, yet this hypothesis has not been tested empirically. We address this by analyzing human intracranial electroencephalogram data recorded during 2 associative memory tasks. We find that neocortical alpha/beta (8 to 20 Hz) power decreases reliably precede and predict hippocampal "fast" gamma (60 to 80 Hz) power increases during episodic memory formation; during episodic memory retrieval, however, hippocampal "slow" gamma (40 to 50 Hz) power increases reliably precede and predict later neocortical alpha/beta power decreases. We speculate that this coupling reflects the flow of information from the neocortex to the hippocampus during memory formation, and hippocampal pattern completion inducing information reinstatement in the neocortex during memory retrieval.
EVALuna2:204498